Port site metastasis following diagnostic laparoscopy for a malignant Gastro-intestinal stromal tumour - Davies, Andrew R (BioMed Central, 2008)
BACKGROUND: Gastro-Intestinal stromal tumours (GISTs) are rare and our understanding of their natural history and optimal treatment are continually evolving. Port site metastasis after laparoscopy for a GIST is an extremely rare phenomenon. CASE PRESENTATION: We report a case with relevant imaging and discuss factors that may have contributed to the development of this isolated metastasis. CONCLUSION: Percutaneous methods of sampling GIST tumours for analysis should be avoided if at all possible. When necessary, prophylactic measures should be utilised to minimise the risk of seeding.